2000
DOI: 10.1046/j.1440-172x.2000.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Migrant farm workers and their families: Cultural patterns and delivery of care in the United States

Abstract: Migrant farm workers and their families represented a critical labour pool in the planting and harvesting of agricultural products in the United States, yet their diminished health status parallel many non‐industrialized communities. The interaction of social, political, environmental and financial obstacles severely restrict access to health care among this community who often perceive insurmountable barriers to navigating the health‐care system. Through the provision of a culturally competent and sensitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…This study found that nurses were constantly challenged to provide appropriate health care to their patients despite their very different cultural and religious backgrounds and unfamiliarity with their patient's cultural practice needs, without recognition of the possible impact on the care the nurses could provide. This is consistent with findings in settings such as the United States, where studies 47,48 revealed that minority groups in the community who had different cultural backgrounds from care providers had not benefited equally from improvements in the health care system. These patients had significantly greater morbidity and mortality rates than the general population, which had been attributed in part to the lack of skills and competency in providers caring for people of diverse cultures and working with teams of culturally diverse backgrounds.…”
Section: Nurse Shortage and Globalizationsupporting
confidence: 88%
“…This study found that nurses were constantly challenged to provide appropriate health care to their patients despite their very different cultural and religious backgrounds and unfamiliarity with their patient's cultural practice needs, without recognition of the possible impact on the care the nurses could provide. This is consistent with findings in settings such as the United States, where studies 47,48 revealed that minority groups in the community who had different cultural backgrounds from care providers had not benefited equally from improvements in the health care system. These patients had significantly greater morbidity and mortality rates than the general population, which had been attributed in part to the lack of skills and competency in providers caring for people of diverse cultures and working with teams of culturally diverse backgrounds.…”
Section: Nurse Shortage and Globalizationsupporting
confidence: 88%
“…These initiatives address several aspects for improving the delivery of health services, including conducting culturally appropriate community health assessments (14,15), using clinic models (79,108), using culture brokers and outreach workers to improve service delivery (52,98), and using lay health advisors (35,102,103). There are no evaluations of these programs or indicators of whether the programs have continued or if they have been replicated in other locales.…”
Section: Farmworker Health Services Programsmentioning
confidence: 99%
“…AgFF workers are primarily from Mexico and Central America, as well as the Caribbean, Asia, and elsewhere. AgFF workers and their families, however, experience numerous barriers to accessing both the general and specialized care they need Bechtel et al, 2008;Kugel and Zuroweste, 2010;Hoerster et al, 2011]. Latinos and other racial and ethnic minorities in the US suffer disproportionately from a number of diseases and health conditions [Keppel, 2007].…”
Section: Introductionmentioning
confidence: 99%